ISLAMISASI PENGETAHUAN - Ambar Hermawan (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2020)
This paper aims to see the resistance shown by Islamic thinkers represented by Syed Naquib Al-Attas, Ismail Raji al-Faruqi, and Fazlurrahman against the development of civilization and intellectualism in the Western world. This study is a literature review that tries to answer questions about the development of Western civilization on Islamic civilization, especially in the intellectual world. This research finds that the development of knowledge in the western world cannot be separated from the methodology and contextualization developed by the West so that it is superior and more developed than the Islamic world